Cognitive Frames in Corporate Sustainability: Managerial Sensemaking with Paradoxical and Business Case Frames - Hahn, Tobias; Preuss, Lutz; Pinkse, Jonatan; Figge, Frank (Academy of Management Review, 2014)
Corporate sustainability confronts managers with tensions between complex economic, environmental, and social issues. Drawing on the literature on managerial cognition, corporate sustainability, and strategic paradoxes, we develop a cognitive framing perspective on corporate sustainability. We propose two cognitive frames—a business case frame and a paradoxical frame—and explore how differences between them in cognitive content and structure influence the three stages of the sensemaking process—that is, managerial scanning, interpreting, and responding with regard to sustainability issues. We explain how the two frames lead to differences in the breadth and depth of scanning, differences in issue interpretations in terms of sense of control and issue valence, and different types of responses that managers consider with regard to sustainability issues. By considering alternative cognitive frames, our argument contributes to a better understanding of managerial decision making regarding ambiguous sustainability issues, and it develops the underlying cognitive determinants of the stance that managers adopt on sustainability issues. This argument offers a cognitive explanation for why managers rarely push for radical change when faced with complex and ambiguous issues, such as sustainability, that are characterized by conflicting yet interrelated aspects.